PENGARUH KARAKTERISTIK CHIEF EXECUTIVE OFFICER (CEO) TERHADAP PENGHINDARAN PAJAK PADA PERUSAHAAN SUB SEKTOR FOOD AND BEVERAGES YANG TERDAFTAR DI BEI TAHUN 2021-2023 - Nafis Muhammad Akbar; H. Mulyadi AR; Surya Fatma (Bajang Institute, 2026)
Abstract: This study examines the influence of Chief Executive Officer (CEO) characteristics on tax avoidance practices in Food and Beverages sub-sector companies listed on the Indonesia Stock Exchange (IDX) during the period 2021–2023. Tax avoidance, defined as a legal effort to minimize corporate tax obligations by exploiting existing regulatory provisions, remains a persistent phenomenon in the corporate landscape. The personal characteristics of a CEO including age, educational background, professional experience, and managerial values are considered key determinants of strategic decision-making, including tax planning policies. This research employed a quantitative approach with causal investigation design using secondary data derived from audited annual financial reports obtained from www.idx.co.id. The total sample consisted of 108 financial reports from 36 companies, selected through a census (saturated sampling) technique. Data were analyzed using simple linear regression with SPSS version 26. The results demonstrate that CEO characteristics have a significant positive effect on tax avoidance, with a beta coefficient of 0.202 and a significance value of 0.004 (p < 0.05). The coefficient of determination (R²) indicates that CEO characteristics account for 13.3% of the variation in tax avoidance behavior. These findings underscore the critical role of executive leadership profiles in shaping corporate tax strategies and highlight the importance of integrating CEO characteristics into tax compliance risk assessments.